2017
DOI: 10.1186/s12905-017-0424-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in drug use between men and women: an Italian cross sectional study

Abstract: BackgroundDrugs are the most important treatment option for most diseases, and the majority of medical consultations result in a prescription. Women and men receive different drug prescriptions and differ in therapeutic response to pharmacological therapy. This disparity is due to biological factors (sex differences) or/and behavior, lifestyle and life experience (gender differences). Sex differences in drug use have been demonstrated in several therapeutic areas; however, there is a lack of overviews on sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The above databases had been previously validated and used to produce drug-utilization information. [20][21][22][23][24][25] Data sources were matched by record linkage analysis through a unique and anonymous personal identification code. Such code was created by a database manager uninvolved in the data analysis, preventing patient identification.…”
Section: Data Sourcementioning
confidence: 99%
“…The above databases had been previously validated and used to produce drug-utilization information. [20][21][22][23][24][25] Data sources were matched by record linkage analysis through a unique and anonymous personal identification code. Such code was created by a database manager uninvolved in the data analysis, preventing patient identification.…”
Section: Data Sourcementioning
confidence: 99%
“…The European Medicines Agency (EMA) may be open to new authorizations because clinical trials with nanomedicines have being increasing in Europe in the last decades. Studies on follow up, use, compliance, and assessment in this area are nevertheless still needed [14][15][16][17]. Regenerative medicine is one of the branches of nanomedicine that is most promising for the approval of new medicines and therapies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative therapeutic approaches to hyperglycemic control are necessary to target hyperglycemia and diabetic complications. In this field, several clinical and experimental studies demonstrated that C-peptide treatment, alone and/or also in combination with insulin, has aphysiological functions, being beneficial in the prevention diabetic complications; studies on follow up, use, and compliance, as reported by recent publications in the area [134][135][136][137] and communication strategies and assessment [138] are nevertheless still needed. A summary of the cytoprotective, antiapoptotic and anti-inflammatory effects of C-peptide, on the renal function and on diabetic neuropathy is provided in Table 1.…”
Section: Discussionmentioning
confidence: 99%